GSM-Based Smart Energy Meter With Arduino Uno - Indra, Win Adiyansyah; Morad, Fatimah; Mohd Yusof, Norfadzlia; Che Aziz, Siti Asma (Research India Publications, 2018)
This paper proposed and demonstrated Smart Energy Meter that the users will be able to monitor their current power consumptions (bill) anytime from anywhere by using their mobile phone via Short Message Services (SMS).It would be a huge beneficial for the customers if they can monitor their energy meter’s power consumptions (bill) on a real-time basis.Arduino UNO, main controller,was the interface between energy meter and Global System for Mobile communication (GSM) module.GSM module connect the energy meter to users’ mobile phone.Real Time Clock (RTC) DS1307 was used to get the real time to count and store the usage into the EEPROM.The program developed in C language with the Arduino syntax in the Arduino IDE.The proposed system demonstrated its capability to check the current usage (bill),notify when reaching the limit,reset the usage (bill) successfully,only via accessing GSM-based mobile phone.